Rock-like material under large diameter SHPB dynamic splitting tension: meso-damage mechanical behavior and stress wave propagation model - Yang, Rongzhou; Xu, Ying; Yu, Meilu; Ge, Jinjin; An, Qi; Ma, Pengying (Frontiers in Materials, 2024)
The mechanical behavior of splitting tensile damage and the law of stress wave propagation of rock-like materials (RLM) are of great significance to further reveal the dynamic disaster mechanism of the deep rock mass. The meso-damage mechanical behavior and stress wave propagation characteristics of RLM disks under impact splitting were studied by using a large diameter split Hopkinson pressure bar (SHPB). In terms of dynamic damage, the splitting tensile stress-compression strain curves of RLM disks obviously showed three stages of mechanical behavior evolution: initial elastic-plastic deformation, pre-peak plastic damage, and post-peak brittle fracture failure. The macro-damage of RLM disks increased with the increase of strain rate. The meso-tensile fracture was the result of both the initial meso-damage and the impact splitting meso-damage. The dynamic splitting damage variable defined based on the damage fracture energy can accurately describe the damage evolution characteristics of impact splitting on RLM disks. In the aspect of stress wave propagation, the peak value of transmission stress showed an advanced effect with the increase of incident stress wave. In the early stage (0 ~ 50 μs), the transmission stress wave ratio () increased with the increase of strain rate, while in the later stage (82 ~ 200 μs), the transmission stress wave ratio () decreased with the increase of strain rate. The stress wave propagation law in the process of impact splitting on RLM disks was clearly revealed based on the stress wave propagation model established by the one-dimensional elastic stress wave theory. Finally, the dynamic mechanical mechanism of splitting damage and fracture of RLM disks under different strain rates was discussed deeply.